Proposal for a Unitary Anatomo-Clinical and Radiological Classification of Third Mobile Window Abnormalities - Reynard, Pierre; Idriss, Samar; Ltaief-Boudrigua, Aicha; Bertholon, Pierre; Pirvan, Andreea; Truy, Eric; Thai-Van, Hung; Ionescu, Eugen C. (Frontiers in Neurology, 2022)
An increased number of otic capsule dehiscence (OCD) variants relying on the third window pathomechanism have been reported lately. Therefore, a characterization of the anatomical structures involved and an accurate radiological description of the third window (TW) interface location have become essential for improving diagnosis and appropriate therapeutic modalities. Materials and methods: Imaging records of 259 patients who underwent, over the last six years, a high-resolution computed tomography (HRCT) of the petrosal bone for conductive hearing loss were analyzed retrospectively. Patients with degenerative, traumatic or chronic infectious petrosal bone pathology were excluded. As cases with a clinical presentation similar to those of a third window syndrome have recently been described in the literature but without these being confirmed radiologically, we thought it necessary to be integrated in a separated branch of this classification as “CT - TMWA”. The same goes for certain intralabyrinthine pathologies also recently reported in the literature, which mimic to some extent the symptoms of a third window pathology. Therefore, we suggest to call them intralabyrinthine TW- like abnormalities. Results: Temporal bone HRCT and, in some cases, 3T MRI of 97 patients presenting symptomatic or pauci-symptomatic, single or multiple, unilateral or bilateral OCD were used to develop this classification. According to the topography and anatomical structures involved at the site of the interface of the third window, a third-type classification of OCD is proposed. Conclusion: A classification reuniting all types of TWMA as the one proposed in this paper would allow for a better systematization and understanding of this complex pathology and possibly pave the way for innovative therapeutic approaches. To encompass all clinical and radiological variants of TMWA reported in the literature so far, TWMAs have been conventionally divided into two major subgroups: Extralabyrinthine (or "true" OCD with three subtypes) and Intralabyrinthine (in which an additional mobile window-like mechanism is highly suspected) or TMWA-like subtype. Along these subgroups, clinical forms of OCD with multiple localisation (Multiple OCD) and those that, despite the fact that they have obvious characteristics of OCD have a negative CT scan (or CT – TMWA), were also included.